2015
DOI: 10.1155/2015/485732
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Serum Inflammatory Response Markers in Newly Diagnosed Non-Small Cell Lung Cancer before Chemoirradiation

Abstract: Purpose. To identify whether the serum's baseline C-reactive protein (CRP) and albumin (Alb) levels related to clinicopathological parameters and overall survival (OS) in non-small cell lung cancer (NSCLC). Methods. In total, 100 consecutive patients (mean age = 68.38 ± 10.85 years) that underwent chemoradiotherapy were studied. Measurements of CRP and Alb were performed before any treatment. Results. Serum CRP levels were significantly associated with histological grade (P < 0.001), TNM stage (P < 0.001), PS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…It was identified that a lower serum ALB level is an independent indicator of a poorer survival in various types of cancer (42). For instance, Tolia et al (43) indicated that the serum ALB level was significantly associated with OS in univariate analysis. Additionally, Jin et al (44) analyzed 101 samples from patients with stage I NSCLC and concluded that patients with low pre-operative ALB levels (<35 g/l) had a significantly poorer survival rate than patients with normal pre-operative serum ALB levels (≥35 g/l).…”
Section: Discussionmentioning
confidence: 99%
“…It was identified that a lower serum ALB level is an independent indicator of a poorer survival in various types of cancer (42). For instance, Tolia et al (43) indicated that the serum ALB level was significantly associated with OS in univariate analysis. Additionally, Jin et al (44) analyzed 101 samples from patients with stage I NSCLC and concluded that patients with low pre-operative ALB levels (<35 g/l) had a significantly poorer survival rate than patients with normal pre-operative serum ALB levels (≥35 g/l).…”
Section: Discussionmentioning
confidence: 99%
“…However, there were few studies regarding the effect of the CAR on prognosis in patients with lung cancer. [1923] Therefore, we collected the available publications and conducted a meta-analysis to investigate whether CAR has a prognostic value in patients with lung cancer in this present study.…”
Section: Introductionmentioning
confidence: 99%
“…Actual activities of the immune functions and homeostasis in medullar immunological microenvironment in the body are di cult to be measured. To date, for different cancer several in ammatory markers has been reported, like CRP (25), albumin (26), neutrophil-to-lymphocyte ratio (NLR) (27), and platelet-tolymphocyte ratio (PLR) (28). Recent studies on the effects of NLR on prognosis of MM patients have been reported (22,23).…”
Section: Discussionmentioning
confidence: 99%